Estudio de la fraseología en Los doze trabajos de Hércules de don Enrique de Villena - Vicente Llavata , Santiago (El Colegio de México, 2020)
This paper aims to contribute to the knowledge of Medieval Hispanic Phraseology by means of the study of phraseological units (prepositional and adverbial locutions), which are represented in don Enrique de Villena’s Los doze trabajos de Hércules. In order to tackle the historical analysis of units characterized by their idiomaticity and fixity, it was decided to base this study on the methodological program proposed by Echenique (2003). As a result of systematic study we are able to verify the historical continuity of some of the phraseological units analysed, as they are disseminated in successive literary and cultural environments in the Iberian Peninsula (especially in Íñigo López de Mendoza’s literary work).